2009
DOI: 10.1002/jmv.21562
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the binding of HCV serum particles to human hepatocytes by E1E2‐specific D32.10 monoclonal antibody

Abstract: The aim of this study was to determine the inhibition of binding activity of the monoclonal antibody (mAb) D32.10 which recognizes a highly conserved discontinuous antigenic determinant (E1:297-306, E2:480-494, and E2:613-621) expressed on the surface of serum-derived HCV particles (HCVsp) of genotypes 1a, 1b, 2a, and 3a. To this end, an in vitro direct cell-binding assay based on the attachment of radiolabeled HCVsp was developed, and Scatchard plots were used to analyze ligand-receptor binding data. HCV adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…A total of 17 linear peptides were reported to be recognized by defined anti-hepatitis C virus (HCV) E1/E2 monoclonal antibodies. Underlined epitopes 1 [11], 5 [12,13], 7 [14], 8 [15,16], 10 [17] and 12 [18,19] are overlapped with six putative linear neutralizing epitopes, and the other 11 epitopes (2, 3, 4, 6, 9, 11, 13, 14, 15, 16 and 17) are targets recognized by well-characterized anti-HCV E1/E2 monoclonal antibodies [20][21][22][23][24][25]. *The first and final positions are numbered with reference to the consensus sequence of the polyprotein of HCV strain H77 (Genbank accession number AB009606).…”
Section: Screening Of Hcv E1/e2-specific Nk-adcc Linear Epitopesmentioning
confidence: 99%
“…A total of 17 linear peptides were reported to be recognized by defined anti-hepatitis C virus (HCV) E1/E2 monoclonal antibodies. Underlined epitopes 1 [11], 5 [12,13], 7 [14], 8 [15,16], 10 [17] and 12 [18,19] are overlapped with six putative linear neutralizing epitopes, and the other 11 epitopes (2, 3, 4, 6, 9, 11, 13, 14, 15, 16 and 17) are targets recognized by well-characterized anti-HCV E1/E2 monoclonal antibodies [20][21][22][23][24][25]. *The first and final positions are numbered with reference to the consensus sequence of the polyprotein of HCV strain H77 (Genbank accession number AB009606).…”
Section: Screening Of Hcv E1/e2-specific Nk-adcc Linear Epitopesmentioning
confidence: 99%
“…Unlike well‐characterized anti‐HCV E2 human mAbs with potent cross‐neutralizing activity, D32.10‐like antibodies have been shown to be associated with spontaneous virus clearance and predictive for complete viral response in chronically‐infected patients under SOC antiviral therapy [9]. The E1E2 epitope targeted by the D32.10 mAb has been shown to be preferentially involved in interactions between the virus and polarized hepatocytes [7]. In the recently proposed 3D‐model of HCV E2 ectodomain (E2e) [19], the E2 segment, aa 613–621, recognized by D32.10 encompassed residues 613–618 important for CD81 binding.…”
Section: Discussionmentioning
confidence: 99%
“…4A and B, lanes 0). As the native antibody, the scFv showed a higher reactivity with the HCVsp isolate 1 (HCV-Lat, GT3) than with the HCV isolate 2 (HCV-Fan, GT1a/1b), independently of the genotype but dependent on surface pattern of HCV particles [6,7]. It is worth noticing that the scFv significantly inhibited in a concentration-dependent manner the binding of IgG D32.10 to both HCVsp isolates (>50% for the isolate 1 and >70% for the isolate 2 at a concentration of 50 lg/ml corresponding to a molecular ratio IgG/scFv = 2) ( Fig.…”
Section: The Scfv Specifically Recognizes Serum-derived Hcv Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that viral clearance is associated with a rapid induction of neutralizing antibodies in the early phase of infection [19], [20], and a large collection of antibodies has been reported to prevent HCV pseudoparticles (HCVpp) or Cell culture-produced HCV (HCVcc) infection[9], [21][29]. One other antibody, named D32.10, plays a protective role by inhibiting the interaction between serum-derived envelope HCV particles and hepatocytes [30], [31].…”
Section: Introductionmentioning
confidence: 99%